Communication with the Other in Jean-Paul Sartre's "L'âge de raison" - Silvester, Rosalind (Acta neophilologica, 2002)
The article analyses conversation between the main characters, Mathieu and Marcelle, in Jean-Paul Sartre's "L'âge de raison" (1945). Interpretation of the material involves recent methodes of discourse analysis and takes into consideration cognitive schemata and the pragmatic intentions of speech acts. A constant objective is to establish whether the interluctors manage to attaineither a metaphysical or morač liberty, when they communicate and whether they are able to maintain this for any length of time. In Sartre's terms, this achievement would mean that each participant keeps his/her reflective quality without becoming an unreflective object for the Other. Communication, in this case, would be considered successful.
Keywords: francoska književnost; French literature; Sartre, Jean-Paul, 1905-1980; tekstna kritika